Reactive oxygen species and cancer: A complex interaction - Saikolappan, Sankaralingam; Kumar, Binod; Shishodia, Gauri; Koul, Sweaty; Koul, Hari K. (Cancer letters, 2019)
Elevated levels of Reactive Oxygen Species (ROS), increased antioxidant ability and the maintenance of redox homeostasis can cumulatively contribute to tumor progression and metastasis. The sources and the role of ROS in a heterogeneous tumor microenvironment can vary at different stages of tumor: initiation, development, and progression, thus making it a complex subject. In this review, we have summarized the sources of ROS generation in cancer cells, its role in the tumor microenvironment, the possible functions of ROS and its important scavenger systems in tumor progression with special emphasis on solid tumors. •ROS is generated from Mitochondrial and Extra-mitochondrial sources and NOX4 appears to play a significant role in ROS generation in Solid tumors.•Tumor cells upregulate antioxidant defense and Redox balance influences tumor progression.•ROS is an integral component of Tumor microenvironment due to Hypoxia Re-oxygenation- and influences immunity.•ROS mediated cell signaling pathways offer attractive targets for therapeutic intervention.